Chemistry revisited: A teacher training workshop on nutrition - Edelsztein, Valeria Carolina (2021)
This work presents a teaching training workshop on human nutrition topics with strong emphasis on the underlying chemical concepts. It was designed according to the Sustainable Conscious Cognitive Learning Model (SCCLM) and framed in a Context-Based Science Education (CBSE) approach. The proposal was implemented with 44 upper secondary school science teachers. It consisted of three phases. First, teachers were presented with 'common-sense' driven sentences on nutrition topics and they were asked if they agreed or disagreed with them. Through an oral discussion, the emergence of the teacher's own cognitive conflicts was promoted in order to trigger subsequent motivation for achieving further knowledge. Next, main scientific ideas and related chemical concepts were presented for each sentence, along with teaching recommendations to complete a CBSE approach. Finally, teachers were asked their opinions on the didactic proposal. Results showed that teachers were motivated to learn beyond their strong initial non-scientific based ideas by questioning the reliability of the information sources. They were also willing to revisit their teaching on some of the canonical concepts of chemistry.